BIOACTIVITY-GUIDED ISOLATION OF MEMORY-ENHANCING COMPOUND FROM CHLOROFORM EXTRACT OF ROOTS OF PLUMBAGO ZEYLANICA LINN. - Uplanchiwar, Vaibhav; Mk, Gupta; Gautam, Rupesh K (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Aim: The main aim of our study is to isolate the active compound from roots of Plumbago zeylanica Linn. by bioactivity-guided isolation and evaluate its memory-enhancing effect by Morris water maze. Methods: Roots were extracted by successive solvent methods by petroleum ether, chloroform, methanol, butanol, and finally, water. Chloroform extract was selected for isolation, and plumbagin was isolated by hexane and ethyl acetate as solvent system. Plumbagin was evaluated by Morris water test, and brain acetylcholine esterase level was measured. Result: Plumbagin showed a significant decrease of escape latency and increase of time spent in target quadrant by mice in Morris water maze indicating improvement of learning and memory. It also significantly decreases the cholinesterase level in the brain. Conclusion: Learning and memory of mice doubtless may be through embarrassment of brain acetyl cholinesterase activity and through involvement of GABA-benzodiazepine pathway. Further detailed study is required to explore the other possible mechanisms for the management of cognitive disorders.